Who Decides Social Policy? : Social Networks and the Political Economy of Social Policy in Latin America and the Caribbean - Bonvecchi, Alejandro; Scartascini, Carlos (Washington, DC: Inter-American Development Bank, 2020)
Who decides the formulation of social policy? What resources do actors bring to decision-making processes? How do those resources position them within decision making networks? This book addresses these questions by combining an institutional political economy approach to policy making with social network analysis of social policy formulation processes in Latin American and the Caribbean. Based on extensive field interviews with governmental and nongovernmental actors, the case studies of social policy formulation in Argentina, Bolivia, The Bahamas, and Trinidad and Tobago show that while in the South American cases societal actors—such as unions and business associations in Argentina, and grassroots organizations in Bolivia—are central actors in the networks, government officials are the main participants in the Caribbean countries. The comparative analysis of the networks of ideas, information, economic resources, and political powers across these cases indicates that differences in the types of bureaucratic systems and governance structures may explain the differences between who decides and what resources underpin their influence in social policy formulation in the region.